Photocatalytic Activity and Characterization of Carbon-Modified Titania for Visible-Light-Active Photodegradation of Nitrogen Oxides - Chun-Hung Huang; Yu-Ming Lin; I-Kai Wang; Chun-Mei Lu (International Journal of Photoenergy)
A variety of carbon-modified titania powders were prepared by impregnation method using a commercial available titania powder, Hombikat UV100, as matrix material while a range of alcohols from propanol to hexanol were used as precursors of carbon sources. Rising the carbon number of alcoholic precursor molecule, the modified titania showed increasing visible activities of NOx photodegradation. The catalyst modified with cyclohexanol exhibited the best activities of 62%, 62%, 59%, and 54% for the total NOx removal under UV, blue, green, and red light irradiation, respectively. The high activity with long wavelength irradiation suggested a good capability of photocatalysis in full visible light spectrum. Analysis of UV-visible spectrum indicated that carbon modification promoted visible light absorption and red shift in band gap. XPS spectroscopic analysis identified the existence of carbonate species (C=O), which increased with the increasing carbon number of precursor molecule. Photoluminescence spectra demonstrated that the carbonate species suppressed the recombination rate of electron-hole pair. As a result, a mechanism of visible-light-active photocatalyst was proposed according to the formation of carbonate species on carbon-modified TiO2.